Assessing the Business Feasibility and Marketing Strategy of Like Mie and Coffee in Batang, Indonesia - Emilia Alfiesyah; Muhammad Taufiq Abadi (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study aims to assess the business feasibility and marketing strategy of Like Mie and Coffee, a local culinary business located in Batang, Indonesia. Using a qualitative descriptive approach, the research evaluates the enterprise through the marketing mix framework (product, price, place, and promotion). Data were collected through observation and in-depth interviews with consumers, managers, and staff to obtain insights into product quality, pricing strategy, location advantages, and promotional effectiveness. The findings reveal that Like Mie and Coffee is a feasible and competitive business supported by innovative products, affordable pricing, a strategic location, and strong digital promotion using social media platforms. The café’s youthful and creative branding has successfully attracted its target market, leading to increased customer loyalty and steady profit growth. The study concludes that business expansion is viable, as demonstrated by the successful opening of a new branch in Semarang. These results highlight the importance of integrating innovation and customer engagement in sustaining small and medium-scale food and beverage businesses in Indonesia’s growing creative economy sector.